SISTEM PENDIDIKAN KARAKTER DI SMA ISLAM AS-SYAFI’IYAH PULO AIR SUKABUMI - Moh. Hifzul Muiz; Aan Hasanah (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
Character education has become a hot discourse in the world of Indonesian education, including in institutions of Islamic education. Although the original idea of ​​character is an old idea as old as the history of education, the emergence of the idea of ​​